أثر دلالات المستويات اللغوية الأربعة في الاجتهاد الفقهي لدى الإمام السالمي في المذهب الإباضي : دراسة وصفية تحليلية - بوسعيدي، حمد محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research highlights the impact of the Arabic language on the ancient and temporary linguists in four linguistic levels: phonemic, morphological, grammatical and lexical. The study conducts in Ijtihad and the deduction of in Islamic rules. The study also focusing on the importance of language in Ijtihad and linguistics that mujtahid must use. The study describes the literarily of Arabic discourse in the past and present. The research will talk about the Ijtihad in Ibadism school of thought by studying its jurists' contributions in language levels. The study devoted to the book of “Ma'ariji Al-Amal 'ala Madarij Al-Kamal Bi Nazm Mukhtasar Al-Khisal” Li Al- 'Imama Nur al-Din al-Salmi with a descriptive and analytical study. The study arrived at conclusions as follow: Ijtihad needs more effort in a specific event, its attainment linked to knowledge of the Arabic language, learning and understanding of what the Arabs used during the revelation of Wahi, at least to a moderate degree. Ibadi jurists excelled in using the language to derive the Deduction rules in Islam. Sheikh Al-Bahlani introduced to address the errors of the phonemic level in the words of prayer. Sheikh Al- 'Utabi increased the interpretations of the lexical level. Imam Al-Salmi did not deviate from the jurists of the regions or the jurists of Ibadism by investigating and tracking jurisprudential issues through his use of linguistic levels to reach a unique jurisprudential opinion.